Educational intervention can improve appropriateness of acid suppression therapy in hospitalized geriatric patients. Issue 1 (2nd January 2019) - Dwivedi, Sankalp; Edukulla, Jaya; Rajendra, Sindhu; Murali, Sandesh; Sorser, Serge A.; Piper, Marc S.; Piper, Michael; Warren, Bradley J.; Ramchandani, Harsha
ABSTRACT: Background : Inappropriate use of acid suppression (AST) therapy may lead to unnecessary harms, especially in the geriatric population. Despite this, AST remains one of the most commonly prescribed medications in the hospital. Therefore, we aimed to assess its prevalence and create educational intervention to improve the appropriateness of inpatient acid suppression therapy. Methods : Using a time-series design, we established a historical control by performing a retrospective chart. Accepted indications for AST were based on those endorsed by the USA Food and Drug Administration and literature review. Inclusion criteria were: (1) age ≥ 65; (2) acid suppression therapy-initiated in the hospital; and (3) patients admitted to the medicine teaching services. We then created an educational intervention, which consisted of lectures and distribution of information pocket cards to residents. Data was collected for two months after the intervention. We used a two-tail fisher exact test and student's t-test to analyze our results. Results : 65% of geriatric patients were inappropriately placed on acid suppression therapy, for which 13% were discharged without further indications. After the educational intervention, the inappropriate use of acid suppression therapy decreased to 45% (P < 0.05). Conclusion : There is a significant overuse of AST in hospitalized geriatric patients. Educational interventions are one potential method that may help improve the appropriateness of acid suppression therapy for elderly inpatients.